Analysis Of Determinants Related To Public Health Visits For Post-Partum Mother During The Covid-19 Pandemic - Dewi Mayangsari; Gunarmi Gunarmi; Fery Agusman Mutoho Mendrofa (Jurnal SMART Kebidanan, 2022)
ABSTRACTPostpartum visits are highly recommended for postpartum mothers to determine their health condition. The postpartum visit target that has not been achieved is influenced by several factors, both predisposing, enabling, and reinforcing factors. The problem of postpartum visits if not treated immediately will have an impact on the occurrence of postpartum complications. The purpose of the study was to determine the factors related to the behavior of postpartum visits during the COVID-19 pandemic at Dukuhwaru Health Center. Methods: this type of research is quantitative with cross-sectional and descriptive correlational design. The population were all post partum mothers normally at the Dismenorea Health Center, in June - July 2022 with total 35 people. Samples were 32 postpartum mothers normally at Dukuhwaru Public Health Center which were taken using a purposive sampling technique. Results: most of the respondents made postpartum visits during the COVID-19 pandemic as many as 23 (71.9%).test results in Fisher exact obtained p-value of age (0.013), education (0.003), parity (0.022), knowledge (0.003), attitude (0.006) and belief/culture (0.035), distance to health facilities (0.006), and family support (0.000) or (p<0.05). Conclusion: There is a relationship between predisposing, enabling, and reinforcing factors with postpartum visit behavior during the COVID-19 pandemic at Dukuhwaru Health Center. Suggestion: It is hoped that postpartum mothers can improve postpartum visit behavior by the time to get early treatment if there are health problems during the postpartum period.  Keywords: COVID-19 pandemic; Post-partum mother; health centre visit.  ABSTRAKKunjungan nifas sangat dianjurkan bagi ibu nifas untuk mengetahui kondisi kesehatannya. Target kunjungan nifas yang belum tercapai dipengaruhi oleh beberapa faktor, baik faktor predisposisi, faktor pemungkin, maupun faktor penguat. Masalah kunjungan nifas jika tidak segera ditangani akan berdampak pada terjadinya komplikasi nifas. Tujuan penelitian adalah untuk mengetahui faktor-faktor yang berhubungan dengan perilaku kunjungan nifas pada masa pandemi COVID-19 di Puskesmas Dukuhwaru. Metode: Jenis penelitian ini adalah kuantitatif dengan rancangan cross-sectional dan deskriptif korelasional. Populasi adalah semua ibu nifas normal di Puskesmas Dukuhwaru pada bulan Juni - Juli 2022 dengan jumlah 35 orang. Sampel adalah 32 ibu nifas normal di Puskesmas Dukuhwaruyang diambil dengan menggunakan teknik purposive sampling. Hasil: Sebagian besar responden melakukan kunjungan nifas pada masa pandemi COVID-19 sebanyak 23 (71,9%). Hasil uji Fisher Exact diperoleh p-value usia (0,013), pendidikan (0,003), paritas (0,022), pengetahuan (0,003), sikap (0,006) dan kepercayaan/budaya (0,035), jarak ke fasilitas kesehatan (0,006), dan dukungan keluarga (0,000) atau (p<0,05). Kesimpulan: Ada hubungan faktor predisposisi, pemungkin, dan penguat dengan perilaku kunjungan nifas pada masa pandemi COVID-19 di Puskesmas Dukuhwaru. Saran : Diharapkan ibu nifas dapat meningkatkan perilaku kunjungan nifas pada saat mendapatkan penanganan dini jika terdapat gangguan kesehatan pada masa nifas. Kata Kunci: Pandemi COVID-19; ibu post-partum; kunjungan Puskesmas.